2019
DOI: 10.1111/cmi.13080
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 release from trophoblasts contributes to inflammation duringBrucella melitensisinfection

Abstract: Brucella melitensis infection causes acute necrotizing inflammation in pregnant animals; however, the pathophysiological mechanisms leading to placentitis are unknown. Here, we demonstrate that high-mobility group box 1 (HMGB1) acts as a mediator of placenta inflammation in B. melitensis-infected pregnant mice model. HMGB1 levels were increased in trophoblasts or placental explant during B. melitensis infection. Inhibition of HMGB1 activity with neutralising antibody significantly reduced the secretion of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(69 reference statements)
0
10
0
Order By: Relevance
“… 16 HMGB1 plays a positive role in a variety of malignant tumor behaviors. 10 , 17 It has been suggested that HMGB1 expression is abnormally high in various tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 HMGB1 plays a positive role in a variety of malignant tumor behaviors. 10 , 17 It has been suggested that HMGB1 expression is abnormally high in various tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…16 HMGB1 plays a positive role in a variety of malignant tumor behaviors. 10,17 It has been suggested that HMGB1 expression is abnormally high in various tumor tissues. This research initially confirmed that HMGB1 expression was upregulated in lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is a ubiquitous nuclear protein that regulates the expression of key genes involved in the pathogenesis of many diseases [ 37 ]. Previous research has shown that HMGB1 released from mouse trophoblasts contributes to inflammation during Brucella melitensis infection [ 38 ]. HMGB1 is reported to induce signalling via the RAGE receptor and the HMGB1/RAGE/cathepsin B signalling pathway, which activates NLRP3-dependent coronary endothelial cell pyroptosis and thus plays an important role in the endothelial damage that occurs in Kawasaki disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, after using anti-HMGB1 antibodies to bind HMGB1 protein, it was found that both NADPH activity and the inflammatory response were inhibited. This indirectly indicates that HMGB1 is closely related to the occurrence of trophoblast inflammation [ 82 ]. In nature, HMGB1 is a ubiquitous and highly conserved protein.…”
Section: Brucella Mediates the Trophoblast Inflammatory Resp...mentioning
confidence: 99%